Respuesta :

Answer:

1x^2y^3/-2

Step-by-step explanation:

You simplify -4/8 into -1/2.

You want to combine/ subtract the exponents with like bases.

x^4-x^2= x^2

y^3- y= y^2

The exponents are positive so you put the exponents on the top.

1x^2y^3/-2

[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{4x^4y^3}{-8x^2y}\implies \cfrac{4}{-8}\cdot \cfrac{x^4y^3}{x^2y^1}\implies -\cfrac{1}{2}\cdot x^4y^3x^{-2}y^{-1}\implies -\cfrac{1}{2}\cdot x^{4-2}y^{3-1} \\\\\\ -\cfrac{1}{2}\cdot x^2y^2\implies -\cfrac{x^2y^2}{2}[/tex]